Effect of Unilateral Transcranial Direct Current Stimulation on Reaction Time in Veterans and Athletes with Disabilities - A.A. Arastoo; Parsaei S.; Sh. Zahednejad; S. Alboghebish; A. BurBur (طب جانباز, 2019)
Aims: Recently, Transcranial Direct Current Stimulation (tDCS) has been considered by researchers to improve various processes. The aim of this study was to investigate the effect of tDCS on reaction time in veterans and athletes with disabilities. Materials & Methods: This semi-experimental study with pre-test post-test design was conducted in 2018 among all veterans and athletes with disabilities, who were members of Veterans and disabled board of Shiraz. 24 veterans and disabled persons of Shiraz athletes were selected by available sampling and allocated to experimental and artificial stimulation (sham) groups. Acquisition stage was held during 3 sessions. In the experimental group, an anode electrode was placed on the C4 and the cathode electrode was placed in the FP1. The stimulation rate was 1.5 milliamps in 20 minutes. In the sham groups, the anode and cathode electrode were placed on the C4 and FP1 points, but the stimulation was discontinued after 30 seconds. After the last session, a post-test was performed. Data analysis was performed by SPSS 22, using independent t-test and Multivariable analysis of covariance. Findings: In the post-test, there was a significant difference between the experimental group and the sham at the simple reaction time and choice reaction time and the performance of the experimental group was better than the sham group (p=0.0001). Conclusion: tDCS can improve the simple and choice reaction time in veterans and athletes with disabilities.